ANALISIS KENAIKAN HARGA KEDELAI TERHADAP PENDAPATAN AGROINDUSTRI TAHU DAN TEMPE DI KELURAHAN KEKALIK JAYA KECAMATAN SEKARBELA KOTA MATARAM - Sri Maryati; Mega Fitri; Ibrahim Ibrahim (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2023)
This study aims to analyze the income of tofu and tempeh agro-industry. This study used a descriptive method with the unit of analysis being businesses that produce tofu and tempeh in Kekalik Jaya Village, Sekarbela District, Mataram City. The research locations were chosen, namely the Kekalik Gerisak, East Kekalik and Kekalik Kijang neighborhoods by purposive sampling in Kekalik Jaya Village, Sekarbela District, Mataram City. The number of artisan respondents was determined by quota as many as 30 respondents and the respondents were taken using the "Accidental Sampling. Types of quantitative and qualitative data. Analysis of the data used is the analysis of costs, income and descriptive analysis related to the increase in the price of soybeans as a raw material for tofu and tempeh agro-industry. The results showed that: The average income of tofu and tempeh agro-industry per process in Kekalik Jaya Village, Sekarbela District, Mataram City is Rp. 853,196 with an average production cost of Rp. 3,799,638 and receipts of Rp. 4,652,833. The increase in the price of soybeans (imported soybeans) as a raw material for the agro-industry of tofu and tempeh from IDR 12,000 per kg increased by 12.5% ​​caused a decrease in income of 32.82%. And if it increases by 25%, it can reduce income by 65.64%. The suggestions that can be given are tofu and tempeh agro-industry craftsmen so they can get around rising raw material prices by not stocking raw materials, varying the products produced so that they have varied and better selling prices and to the government through related agencies so they can increase production and soybean productivity so that it can be a substitute for imported soybeans.